A symmetrical Cascaded H-bridge Multilevel Inverter used as shunt active power filter for ideal and deteriorated voltage conditions - Mortezaei, Ali; Godoy Simoes, M.; Busarello, Tiago D. C.; Durra, Ahmed Al; Marafao, Fernando P. [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2016)
This paper discusses the use of a Cascaded H-bridge Multilevel Inverter (CHMI) as shunt active power filter (SAPF) for selective disturbing currents compensation. The main feature of the proposed approach is the use of independent DC sources, with reduced DC-link voltages, which makes such a topology an ideal candidate for medium and high power applications with increased reliability. The developed control strategy regulates independent DC-link voltages in each H-bridge cell and allows selective compensation under a variety of voltage conditions without requiring any kind of reference-frame transformation. The selective compensation strategies are based on the decompositions proposed in the Conservative Power Theory (CPT), which result in several current-related terms associated with specific load characteristics. These current components are independent from each other and are used to define different compensation strategies, which can be selective in minimizing particular effects of disturbing loads. In order to validate the possibilities and performance of the proposed control strategies, a three-phase grid with unbalanced nonlinear loading and negligible line impedance was simulated in PSIM considering ideal and deteriorated voltage conditions.
Keywords: Active power filters; Compensation strategies; Harmonics; Multilevel inverter; Reactive compensation; Selective compensation; Unbalance compensation